2015
DOI: 10.1097/rhu.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anti–Tumor Necrosis Factor Therapy Administered Subcutaneously and Associated Factors in Patients With Rheumatoid Arthritis

Abstract: The overall nonadherence with subcutaneous biologic therapy is relatively high among RA patients and should be taken into account when a patient's response to treatment is unsatisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
3
31
1
3
Order By: Relevance
“…Persistence on treatment has been identified as a surrogate for treatment effectiveness; however, in the absence of patient level data in our study, it is not possible to determine whether these results are consistent with the published data reflecting real‐world efficacy or representative of the underlying characteristics of specific patient populations receiving specific treatments as restricted under the Australian funding rules for bDMARDs…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Persistence on treatment has been identified as a surrogate for treatment effectiveness; however, in the absence of patient level data in our study, it is not possible to determine whether these results are consistent with the published data reflecting real‐world efficacy or representative of the underlying characteristics of specific patient populations receiving specific treatments as restricted under the Australian funding rules for bDMARDs…”
Section: Discussioncontrasting
confidence: 58%
“…Persistence on treatment has been suggested as a surrogate for treatment effectiveness . There is limited data on treatment persistence by mode of action in the same RA population.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies 3 , 15 17 suggested that higher medication adherence with RA exhibits achievement of lower disease activity during treatment with drugs. However, these results were challenged and not confirmed by other studies, 18 20 and no systematic review was conducted to quantify the association of medication adherence and disease activity in RA using meta-analysis techniques. The objectives of this systematic review were: 1) to find the relationship between medication adherence and disease activity among adult RA patients; 2) to provide a summary of the methods used to define medication adherence and disease activity in RA, and 3) to summarize supportive measures to enhance medication adherence.…”
Section: Introductionmentioning
confidence: 87%
“…31 With regard to adherence, which is a related but different concept, previous studies suggested a lower adherence among older patients. 41 Both adherence and persistence were reported to be related to treatment satisfaction, 42 which underlines the relevance of defining persistence as a treatment goal in RA.…”
mentioning
confidence: 99%